Fire blight in Hungary between 1996 and 2003 - Mike, Zs. (International Journal of Horticultural Science, 2004)
Shoot blight of pome fruits caused by Erwinia amylovora, i.e. fire blight, is present in numerous countries of Europe. The disease must have entered into Hungary in the middle of the 1990’s and it was first noted and, respectively, identified in 1996 (Bacs-Kiskun county). The losses caused by the pathogen appeared — in orchards and scattered sites of production — in four counties, namely Bacs-Kiskun, Baranya, Bekes and Csongrad at the beginning. From June 1996, a process of eliminating infected parts started in the course of a large action performed under the control of the Department of Plant Protection and Agro-Environmental Economy of the Ministry of Agriculture, under the direction of the plant protection inspectors of the then existing Stations of Plant Health and Soil Conservation. The ’operation’ against the disease commenced by cutting back out the infected parts of the canopy and, grubbing them out, respectively. As for the spread of the pathogen (1996-1998) it could be observed that the disease entered into Hungary from the south, south-east and then it also spread into the middle part of the country. As a result of adequate official action and efforts as well as of adequate chemical and antibiotic treatments, moreover because of the introduction of more modern technologies of plant cultivation and those of plant protection it can be reported on that the pathogen hardly appears or does not occur at all on the northern, north-western part of the country. The infection also appears mainly on the parts east of the Danube. Cultivars less susceptible or non-susceptible to the disease are planted in recently established orchards what is also a considerable factor in respect of preventing spread of the pathogen.